1999
DOI: 10.1042/cs19980269
|View full text |Cite
|
Sign up to set email alerts
|

Soccer players under regular training show oxidative stress but an improved plasma antioxidant status

Abstract: Physical activity is known to induce oxidative stress in individuals subjected to intense exercise. In this study, we investigated the lipoprotein profile and the plasma antioxidant status in a group of soccer players engaged in a regular training programme. As was expected for aerobic exercise, high-density lipoprotein-cholesterol (HDL-C) and HDL3-C levels were significantly increased in the sportsmen (P<0.05). Total plasma antioxidant capacity was 25% higher in sportsmen than in controls (P<0.005). According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
64
3
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 0 publications
14
64
3
6
Order By: Relevance
“…This finding is in agreement with a previous study (Schippinger et al 2002), thus suggesting that the antioxidant supplementation, together with the training program, although not ROMs reactive oxygen metabolites, TAS total antioxidant status, GR glutathione reductase, Hsp70 heat shock protein 70, NO nitric oxide able to increase TAS was at least effective in ''containing'' the production of peroxides in our athletes (Sacheck and Blumberg 2001). However, it has been previously reported also that soccer players showed significantly higher TAS compared to the controls (Brites et al 1999). This conflicting result may probably reflect some differences between the two study populations of soccer players, including the duration and intensity of the exercise or training program, the age, the diet and health status of each individual, all these factors being able to diversely affect TAS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with a previous study (Schippinger et al 2002), thus suggesting that the antioxidant supplementation, together with the training program, although not ROMs reactive oxygen metabolites, TAS total antioxidant status, GR glutathione reductase, Hsp70 heat shock protein 70, NO nitric oxide able to increase TAS was at least effective in ''containing'' the production of peroxides in our athletes (Sacheck and Blumberg 2001). However, it has been previously reported also that soccer players showed significantly higher TAS compared to the controls (Brites et al 1999). This conflicting result may probably reflect some differences between the two study populations of soccer players, including the duration and intensity of the exercise or training program, the age, the diet and health status of each individual, all these factors being able to diversely affect TAS.…”
Section: Discussionsupporting
confidence: 94%
“…Our data evidenced that serum GR activity was significantly enhanced in the players compared to the controls. Therefore, it is conceivable that the specific training regimen, although not able to increase TAS for the above-reported reasons (Brites et al 1999), was at least able to induce an up-regulation of GR in our soccer players.…”
Section: Discussionmentioning
confidence: 93%
“…As well, the enhancement of antioxidant vitamin status during oxidative stress observed in this study is not an uncommon phenomenon. For example, humans had improved antioxidant status including elevation of vitamin E concentration during exercise (which is associated with oxidative stress) (Brites 1999;Cazzola et al 2003). In fish, Palace et al (1994) reported that exposure of lake char to low dose polychlorinated biphenyl congener 126 increased the concentration of a-tocopherol Fig.…”
Section: Results and Dicussionmentioning
confidence: 99%
“…Many studies have compared the antioxidant status of trained and untrained subjects at rest, but, to our knowledge, except the study of Ørtenblad and coworkers (1997) that analysed blood antioxidant status in untrained and jump-trained humans following six bouts of 30-s continuous jumping, no study has compared the athletes' and non-athletes' pro/antioxidant responses to acute exercise of maximal intensity. SOD, enzyme of the first line of defence in RBCs was most commonly found to be the one that changes under the influence of both acute and chronic exercise (Miyazaki Groussard et al 2003;Ookwara et al 2003) and the one that differentiates between well trained subjects and controls (Brites et al 1999;Evelson et al 2002;Metin et al 2003). Our study confirmed this observance, since young handball players had significantly higher basal SOD activity compared with non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that well trained subjects have more efficient ADS compared with sedentary subjects, however, those studies compared only the basal (resting) levels of pro/antioxidants in blood of athletes and non-athletes (Ørtenblad et al 1997;Balakrishnan and Anuradh 1998;Brites et al 1999;Evelson et al 2002;Cazzola et al 2003;Gougoura et al 2007;Yamaner 2010). Thus, the primary aim of our study referred to the comparison of the effects of acute maximal intensity exercise on pro/antioxidant response in athletes and non-athletes.…”
Section: Introductionmentioning
confidence: 99%